Implementation of a Vocational Training Program in Realizing Social Inclusion for Persons with Disabilities at the People's Welfare Bureau of East Java Province - Putri Anggraeni Cahyaningrum; Fitrotun Niswah; Meirinawati M; Neny Ayu Nourmanita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the implementation of vocational training programs in promoting social inclusion and to identify the supporting and inhibiting factors affecting their implementation at the Bureau of Public Welfare of East Java Province. This study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation and were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The results indicate that the implementation of vocational training programs for persons with disabilities has provided formal access through the provision of inclusive regular training programs. However, the implementation has not fully met the principles of accessibility, participation, equity, and accountability. Supporting factors include institutional commitment, inter-agency coordination, a flexible training system, the utilization of technology, and social support. Meanwhile, inhibiting factors consist of limited accessible facilities, inadequate assistance services, and the absence of service standards specifically designed to accommodate the needs of participants with disabilities. It is concluded that the implementation of vocational training programs for persons with disabilities in East Java Province has expanded formal access for persons with disabilities; however, the principles of social inclusion have not yet been fully institutionalized in program implementation.